Cardiac anomalies in Axenfeld–Rieger syndrome due to a novel FOXC1 mutation12. Issue 1 (14th December 2012) - Gripp, Karen W.; Hopkins, Elizabeth; Jenny, Kim; Thacker, Deepika; Salvin, Jonathan
Abstract Axenfeld–Rieger syndrome (ARS) is an autosomal dominant condition characterized by ophthalmologic anterior segment abnormalities and extraocular findings including dental anomalies and redundant periumbilical skin. Intragenic mutations in the homeobox gene PITX2 or the transcription factor encoding FOXC1 were identified, and genomic rearrangements encompassing either gene also cause ARS. A molecular etiology is identified in 40–60%. Extraocular anomalies occur more often with intragenic PITX2 than FOXC1 mutations. We report on a patient with infantile glaucoma presenting at age 21 months with congestive heart failure due to a dysplastic arcade mitral valve necessitating valve replacement, and mildly hypoplastic left ventricular outflow tract and aortic arch. Family history included early onset glaucoma in four relatives; congenital hip dysplasia requiring surgery in three; and an atrial septal defect in the affected maternal grandmother. Despite the absence of dental or umbilical abnormalities, anterior chamber abnormalities consistent with ARS were present in affected individuals. Molecular testing revealed a novel FOXC1 mutation (c.508C>T; p.Arg170Trp) in the proband and his affected mother; other family members were unavailable. A literature review revealed four reports of congenital heart disease associated with intragenic FOXC1 mutations, and none with intragenic PITX2 mutations. Previously, mouse studies showed Foxc1 (Mf1) expression in the developing valves and atrial septum, supporting a causal relationship of FOXC1 mutations for valvar anomalies and ASD. Hip dysplasia in three family members suggests a role for FOXC1 in the femoral head dysplasia of de Hauwere syndrome with 6p25 deletions. Further reports of clinical and molecular diagnoses will clarify genotype–phenotype correlation. © 2012 Wiley Periodicals, Inc.